The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1001/jamanetworkopen.2021.18508
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Measles and Mumps Antibodies Among Individuals With Cancer

Abstract: IMPORTANCE Although patients with cancer are at an increased risk of infection-related complications, few studies have characterized their vulnerability to measles and mumps. Given the recent outbreaks and increased community vaccine hesitancy, understanding measles and mumps immunity within this population is vital. OBJECTIVESTo identify a point prevalence estimate of protective measles and mumps antibodies among ambulatory patients with cancer. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…We explored recall response to measles, where we observed that 81% of subjects were seropositive for measles serum antibodies, two subjects (Subject 3 and 10) are currently on active treatment with bcl-2 inhibitor and BTKi respectively and one is treatment naïve. This is a slightly higher response rate than was observed in a recent cross-sectional study of 959 patients 24 which detected a 63% measles seropositivity rate in subjects with hematological malignancies. The antibody response to measles seems largely unaffected in CLL subjects, indicating that LLPCs responsible for maintaining circulating serum antibodies remain stable throughout CLL immune dysfunction and treatment.…”
contrasting
confidence: 61%
“…We explored recall response to measles, where we observed that 81% of subjects were seropositive for measles serum antibodies, two subjects (Subject 3 and 10) are currently on active treatment with bcl-2 inhibitor and BTKi respectively and one is treatment naïve. This is a slightly higher response rate than was observed in a recent cross-sectional study of 959 patients 24 which detected a 63% measles seropositivity rate in subjects with hematological malignancies. The antibody response to measles seems largely unaffected in CLL subjects, indicating that LLPCs responsible for maintaining circulating serum antibodies remain stable throughout CLL immune dysfunction and treatment.…”
contrasting
confidence: 61%
“…Of those, two subjects (Subject 3 and 10) are currently on active treatment with bcl-2 inhibitor and BTKi respectively and one subject is treatment naïve. This is a slightly higher response rate than was observed in a recent cross-sectional study of 959 patients 34 which detected an overall 75% measles seropositivity rate in cancer subjects and lower (63% seropositivity) in those with hematological malignancies. Overall, the antibody response to measles seems largely unaffected in CLL subjects, indicating that long-lived plasma cells responsible for maintaining circulating serum antibodies remain stable throughout CLL immune dysfunction and treatment.…”
Section: Discussioncontrasting
confidence: 62%
“…In this investigation, we explored the recall response to measles virus, a common childhood antigen exposed to either through vaccination or natural infection in subjects born before 1963. 34 Here, we observed that 81% of our subjects were seropositive for measles serum antibodies, with all but three subjects exhibiting a response above background (limit of detection). Of those, two subjects (Subject 3 and 10) are currently on active treatment with bcl-2 inhibitor and BTKi respectively and one subject is treatment naïve.…”
Section: Discussionmentioning
confidence: 51%
“…Twenty‐five percent of cancer patients lack protective antibodies for measles and 38% lack antibodies for mumps; furthermore, hematopoietic cell transplantation (HCT) is associated with 50% lower seroprevalence compared with cancer patients with no previous HCT 1 . The reported probability for being seronegative for measles, mumps, and rubella at 5 years after allogeneic HCT are 60, 73, and 52%, respectively; 2 and prior studies suggest that virus‐specific long‐term B‐cell memory function is not maintained, regardless of the immune status of the donor 2 …”
Section: Introductionmentioning
confidence: 99%